Minimum Information about T Regulatory Cells: A Step toward Reproducibility and Standardization - Fuchs, Anke; Gliwiński, Mateusz; Grageda, Nathali; Spiering, Rachel; Abbas, Abul K.; Appel, Silke; Bacchetta, Rosa; Battaglia, Manuela; Berglund, David; Blazar, Bruce; Bluestone, Jeffrey A.; Bornhäuser, Martin; et al. (Frontiers in Immunology, 2018)
Cellular therapies with CD4+ T regulatory cells (Tregs) hold promise of efficacious treatment for the variety of autoimmune and allergic diseases as well as post-transplant complications. Nevertheless, current manufacturing of Tregs as a cellular medicinal product varies between different laboratories, which in turn hampers precise comparisons of the results between the studies performed. While the number of clinical trials testing Tregs is already substantial, it seems to be crucial to provide some standardised characteristics of Treg products in order to minimize the problem. We have previously developed reporting guidelines called MITAP (Minimum Information about Tolerogenic Antigen-Presenting cells), which allows the comparison between different preparations of tolerance-inducing antigen-presenting cells. Having this experience, here we describe another minimum information model developed for Tregs (MITREG). It is important to note that MITREG does not dictate how investigators should generate or characterize Tregs, but it does require investigators to report their Treg data in a consistent and transparent manner. We hope this will, therefore, be a useful tool facilitating standardized reporting on the manufacturing of Tregs, either for research purposes or clinical application. This way MITREG might also be an important step towards more standardised and reproducible testing of the Tregs preparations in clinical applications.